Perilaku Petani Anggota Subak terhadap Program Optimasi Lahan (OPLA) pada Budidaya Tanaman Padi (Kasus Subak Tegan, Kelurahan Kapal, Kecamatan Mengwi, Kabupaten Badung) - PUTRA, I NENGAH SUWARNADI; PUTRA, I GEDE SETIAWAN ADI; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
Farmers Behavior of Subak Members toward the Land Optimization Program (OPLA) on Rice Cultivation (the Case of Subak Tegan, Kapal Village, Mengwi District, Badung Regency) Food security is very important since it is one of the determining factors in the national stability of a State in the fields of economy, security, political and social. Bali has an organization called Subak, which supports activities in the agricultural sector. The government of Badung regency through the Department of Agriculture, Plantation and Forestry will implement special measures, Optimization of Land (OPLA) by providing inputs. Farmers behavior certainly indicates a different view regarding the Land Optimization program. The purpose of this research is to determine the level of knowledge, attitude and application of farmers to land optimization program (OPLA) on rice cultivation in Subak Tegan. This research was conducted in Subak Tegan, Kapal Village, Mengwi District, Badung Regency. The population of Subak Tegan is 389 people. Determination of the research sample used simple random sampling method. The total respondents taken are 39 people. The results show that the knowledge of farmers on OPLA program is under good category with an achievement score of 78.68%. As regard to the farmers' attitude and application of the OPLA program, the result showed an excellent category with achievement score of 85.38% and the achievement score of implementation is 85.00%. The farmer behavior of Subak Tegan members toward the Land Optimization program (OPLA) belongs to good category with an achievement score of 83.02%. Based on the results of study the agricultural extension counselorare expected to apply a persuasive approach, explain the uniqueness, advantages, benefits, and provide guidance until the independent farmers actually implement the OPLA program.
Keywords: behavior, subak, land optimization, rice